2011
DOI: 10.17705/1cais.02926
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Researcher Publication Productivity in the Leading Information Systems Journals: A 2005–2009 Update

Abstract: This study is an update of a previous scientometric study that examined the leading Information Systems (IS) researchers, their university affiliations, and the universities that supply them. We provide geographical comparisons of researcher affiliations for the AIS regions and for North American versus global institutions, along with a comparison of prior and current results. Our analysis shows that coauthorship is increasing in the top three IS journals and that most of the leading researchers continue to af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…However, critical and interpretive research is now more widely accepted by the IS community (Klein & Myers, 1999;Myers & Klein, 2011;Walsham, 2006). Additionally, calls for a larger basket of top IS journals (Clark, Au, Walz, & Warren, 2011) demonstrates the desire for inclusivity. Our method is intended for IS research communities that desire to create a forum for open debate and discussion of taken-forgranted assumptions through academic publications.…”
Section: Clarifying Our Critical Positionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, critical and interpretive research is now more widely accepted by the IS community (Klein & Myers, 1999;Myers & Klein, 2011;Walsham, 2006). Additionally, calls for a larger basket of top IS journals (Clark, Au, Walz, & Warren, 2011) demonstrates the desire for inclusivity. Our method is intended for IS research communities that desire to create a forum for open debate and discussion of taken-forgranted assumptions through academic publications.…”
Section: Clarifying Our Critical Positionmentioning
confidence: 99%
“…In most cases, researchers should collect publications from the discipline's top journals. The top journals represent mainstream perspectives (Clark et al, 2011) and tend to exert the greatest influence on tenure decisions (Straub, 2009). Top journals are also more highly read and cited; therefore, top journals are more likely to carry ideological assumptions to a wider audience.…”
Section: Analysis Stepsmentioning
confidence: 99%
“…Institutional rankings are determined by the number of articles published by authors affiliated with the institution. For example, institutions have been ranked using this approach in a variety of academic disciplines such as Supply Chain Management (Maloni, Carter, and Kaufmann 2012), Transportation and Logistics (Carter et al 2005), Accounting (Chan, Chen, and Cheng 2005;Mathieu and McConomy 2003), Economics (Conroy et al 1995;Coupe 2003;Jin and Hong 2008;Scott and Mitias 1996), Finance (Heck, Cooley, and Hubbard 1986;Heck 2007;Lasser and Rydqvist 2006;Sousa and Vieira 2011), Information Systems (Clark and Warren 2006;Clark et al 2011), Behaviour Analysis (Shabani et al 2004), Biology (Grant et al 2007), Criminal Justice (Fabianic 2002;Sorensen and Pilgrim 2002;Steiner and Schwartz 2006), Psychology (Feingold 1989;Mahoney et al 2010), Real Estate (Chan et al 2008;Turnbull 2000, 2002;Jin and Yu 2011;Urbancic 2007), Rehabilitation Counselling (West, Armstrong, and Ryan 2005), Science Education (Barrow, Settlage, and Germann 2008), and Special Education (Miller and Maddux 1991). Additionally, in the area of Finance, Heck (2007) and Heck, Cooley and Hubbard (1986) considered the ranking of institutions based on the affiliation of authors as well as where the researchers received their Ph.D. training.…”
Section: Related Literaturementioning
confidence: 99%
“…Athey and Plotnicki [4] used a similar approach in evaluating the productivity of IS faculty and programs between 1992 and 1996 using articles published in the top ten IS journals. Most recently, Clark et al [6] performed an IS publication productivity study and found that co-authorship is increasing in the premier IS journals and that the proportion of researchers in these journals affiliated with North American universities is decreasing. None of the previous studies specifically looked at IS educational research productivity.…”
Section: Research Productivity In Business Educationmentioning
confidence: 99%